Eksistensi Komunitas Srikandi Pasundan bagi Transpuan - Ehza Alifan Hanif; Mirna Nur Alia Abdullah; Siti Komariah (Ideas Publishing, 2022)
The existence of transgender women (transwomen) cannot be taken for granted by society and even by their families because they have values and norms that are contrary to society. This thing make transwomen leave their families and environment and choose to join the transwomen community, one of them is the Srikandi Pasundan Community. The purpose of this study is to get an overview of the Srikandi Pasundan Community strategy in maintaining the existence of transwomen. Theory which used in this study, that is community development theory which put forward by Phillips and Pitman and social capital theory which put forward by Robert Putnam. Those theories could analyze existence of Srikandi Pasundan Community which is transwomen community started from background behind and position community, contribution of community for transwoman, impact of existence of community. This study used approach qualitative with method studies case for get results and analysis data. Technique collection data that conducted that is observation, Interview, and documentation. Results from study this showing that existence of Srikandi Pasundan Community have contribution and impact positive for transwomen and community.